Mortality Analysis of Adult Burn Patients - Martina, Nungki Ratna; Wardhana, Aditya (Jurnal Plastik Rekonstruksi, 2013)
Backgrounds: Among burn patient, adult patient in productive age took a large number in statistic. Fire related to domestic accident and in workplace are the main source of burn incidences. A careful review of burn mortality of adult patient in Burn Unit of Ciptomangunkusumo Hospital is presented in this paper. The aim is to make a critical analysis of mortality in our burn centre with a view to finding possible ways of improving the care given to our patients and suggesting ways of reducing mortality. Patients and Method: A descriptive analysis study was done to analyze data collected by the review of medical records of the patients hospitalized to our Burn Center for burn injury from Januari 2011– Desember 2012. Parameters investigated include patients’ demographics, data for etiology and extent of burn injury, cause of death and the mortality were tabulated, computerized and analyzed. Result: During this 2-year period, 275 patients were admitted, 203 patients were adults. Number of death in adult patient were 76 patients (27,6%). Among the died patients, seventy-eight percent caused by flame, electrical burn injury (14%), hot water (4%), chemical (3%), metal (1%). Almost all burn extent was deep dermal (2nd degree) and full thickness (3rd degree). The cause of death including septicaemia (42,1%), multiple organ failure (31,6%), systemic inflammatory response syndrome (17,6%), and acute respiratory distress syndrome (8,7%). Conclusion: In order to implement a successful burn injury prevention program, it is important to focus on selected issues. A few specific recommendations can be suggested based on these epidemiological features. Our ongoing efforts are to promote and support prevention program and look for changes in the incidence of burn injury.